2020
DOI: 10.3390/ijms21134658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lycium barbarum Polysaccharides on Pyroptosis-Associated Amyloid β1-40 Oligomers-Induced Adult Retinal Pigment Epithelium 19 Cell Damage

Abstract: Age-related macular degeneration (AMD) is a sight-threatening disease with limited treatment options. We investigated whether amyloid β1-40 (Aβ1-40) could cause pyroptosis and evaluated the effects of Lycium barbarum polysaccharides (LBP) on Aβ1-40 oligomers-induced retinal pigment epithelium 19 (ARPE-19) damage, which is an in vitro AMD model. Aβ1-40 oligomers verified by Western blot were added to ARPE-19 cells with or without 24 h LBP treatment. Aβ1-40 oligomers significantly decreased ARPE-19 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…As LPS is not associated with AMD, this in vitro model is possibly invalid to mimic AMD. Instead, Amyloid beta 1-40 oligomers-exposed non-LPS-primed RPE cell [ 53 ] may more likely mimic AMD. Another study showed that amyloid beta 1-40 oligomers at a high concentration (25 μM) lowered ARPE-19 cell viability after 24 hours of stimulation [ 38 ].…”
Section: Disease Mechanisms Of Amdmentioning
confidence: 99%
See 3 more Smart Citations
“…As LPS is not associated with AMD, this in vitro model is possibly invalid to mimic AMD. Instead, Amyloid beta 1-40 oligomers-exposed non-LPS-primed RPE cell [ 53 ] may more likely mimic AMD. Another study showed that amyloid beta 1-40 oligomers at a high concentration (25 μM) lowered ARPE-19 cell viability after 24 hours of stimulation [ 38 ].…”
Section: Disease Mechanisms Of Amdmentioning
confidence: 99%
“…Programmed cell death (PCD) plays an important role in response to stress and the regulation of homeostasis and diseases. Apart from the classical apoptosis, recent basic science studies also discovered novel PCD such as pyroptosis [ 53 ], necroptosis [ 88 ] and ferroptosis [ 57 ], which may contribute to the RPE cell death in AMD ( Figure 2 ). A comparison of the three novel programmed cell deaths has been listed in Table 1 .…”
Section: Overview Of Novel Programmed Cell Death (Pcd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have suggested that certain natural polysaccharides, particularly those from plants, possess unique biological activities for the ocular system. Lycium barbarum polysaccharides have been reported to ameliorate dry eye disease, prevent oxidative damage in human trabecular meshwork cells, and preserve the function, ganglion cells, and pigment epithelium cells of the retina ( Yang et al, 2017 ; Yang M. et al, 2020 ; Chien et al, 2018 ; Lakshmanan et al, 2019 ; Liu and Zhang, 2019 ; Liu L. et al, 2020 ). Carboxymethyl Terminalia catappa polysaccharides show therapeutic effects in the cornea from blue light-emitting diodes.…”
Section: Bioactive Polysaccharide-based Nanocarriers For Ocular Delivmentioning
confidence: 99%